The Effect of Asset Structure, Profitability and Liquidity on the Capital Structure of the Manufacturing Industry Sector - Erna Sugiarti; Nanan Sunandar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The motivation behind this research is to find out the variables that affect capital structure, and this examination is a quantitative report using optional information handled through various methods of multiple linear regression investigation using SPSS26. Asset structure (X1), profitability (X2), and liquidity (X3) are independent research variables, while capital structure (Y) is the research dependent variable. Comparison of Asset Structure, Return On Assets (ROA), Current Ratio (CR), and Debt To Equity Ratio (DER) as measuring tools. The participants in this study were food and beverage companies listed on the Indonesia Stock Exchange in 2019 – 2021, while the sample this study consisted of 15 food and beverage companies listed on the Indonesia Stock Exchange in 2019 - 2021. Purposive sampling was used to take samples, this study found that partially asset structure and profitability have a negative impact on capital structure, while liquidity has a positive impact on capital structure. Then if simultaneously asset structure, profitability, and liquidity have a positive effect on capital structure.